A systematic review and mixed-methods synthesis of the experiences, perceptions and attitudes of prison staff regarding adult prisoners who self-harm. Issue 4 (6th July 2022) - Hewson, Thomas; Gutridge, Kerry; Bernard, Zara; Kay, Kathryn; Robinson, Louise
Abstract : Background: Self-harm, including suicide, is common among prisoners. Staff attitudes and perceptions regarding self-harm may affect quality of care and patient safety. Aims: To systematically review the experiences, perceptions and attitudes of staff in adult prisons regarding self-harm. Method: Systematic searches of EMBASE, Medline, PsycINFO and CINAHL databases were conducted, and supplemented by hand-searching and grey literature review, to identify relevant English-language articles published since the year 2000. Articles were screened by two authors and evaluated with standardised quality appraisal tools. Qualitative data were analysed thematically, whereas quantitative data were narratively synthesised because of high study heterogeneity. Results: Two thousand articles were identified, of which 32 were included, involving 6389 participants from five countries. Most studies were moderate ( n = 15) or poor ( n = 10) quality, and seven were rated as good quality. Staff frequently witnessed self-harm and described multiple perceived risk factors and causes of this. Perceptions that self-harm is 'manipulative' or 'attention-seeking' were associated with hostility toward prisoners and lower quality of care. Perceived barriers to preventing and managing self-harm included low staffing levels, prison environments and culture, poor staff confidence and insufficient training. The importance of multidisciplinary teamwork and building staff–prisoner relationships were highlighted. Staff occasionally experienced intense psychological reactions to self-harm, which resulted in adaptive or maladaptive coping that influenced their capacity to care. Conclusions: There are mixed attitudes and perceptions toward self-harm among prison staff. Further training, support and resources are required to protect staff's well-being and improve self-harm prevention and management in prisons.